Analisis Problematika Pengembangan Kampung Wisata Ramah Anak di Desa Cikole Berdasarkan Level Mikrosistem Teori Ekologi - Ihsan, Helli; Selfiyani Lestari; Sri Maslihah; Anastasia Wulandari (LPPM UNINUS, 2023)
The development of a child-friendly tourist village in Cikole Village cannot yet be carried out optimally. The aim of this service program is to analyze the problems that occur in Cikole village in developing a child-friendly tourist village based on the microsystem level of ecological theory. The method used in this service is through focus group discussions. The data obtained were analyzed using thematic analysis based on the microsystem level of ecological theory. The results show that there are several main problems that are obstacles to the development of a child-friendly tourist village in Cikoleh Village, including the lack of a clear vision and mission, no organization capable of driving the program, lack of funding for program realization, and obstacles in mobilizing residents. Some of these obstacle points become initial data that can be used in designing further interventions. Based on analysis using ecological theory, it can be concluded that the problems faced in developing a child-friendly tourist village in Cikole Village occur at the ecological microsystem level so that intervention needs to be carried out comprehensively..